The conflict between national security and individual privacy rights in Malaysia - Where do the courts stand? / Md. Zubair Kasem Khan - Kasem Khan, Md. Zubair (Universiti Teknologi MARA, Pulau Pinang & Pusat Penerbitan Universiti (UPENA), 2015)
The existence of sophisticated neo-technologies in this information and communication age provides the Malaysian government a spectrum of measures to ensure security at the national level. These technology-based measures are however also a cause of concern among Malaysians when it comes to individual privacy rights. This paper attempts to conceptualize the divergent notions of privacy and security and to justify the need for these two opposing notions in respect of electronic-based security measures in both public and private premises in Malaysia. In considering these divergent notions, this paper will consider the perception of the courts of Malaysia as well as courts of other developed countries concerning the use of electronic-based measures for ensuring national security and the conflict with individual privacy rights. This study will also provide a solution for the harmonization between the conflicting notions of national security and individual privacy rights.